Organoclay hybrid materials as precursors of porous ZnO/silica-clay heterostructures for photocatalytic applications - Akkari, Marwa; Aranda, Pilar; Ben Haj Amara, Abdessalem; Ruiz-Hitzky, Eduardo (Beilstein Journal of Nanotechnology, 2016)
In this study, ZnO/SiO2-clay heterostructures were successfully synthesized by a facile two-step process applied to two types of clays: montmorillonite layered silicate and sepiolite microfibrous clay mineral. In the first step, intermediate silica–organoclay hybrid heterostructures were prepared following a colloidal route based on the controlled hydrolysis of tetramethoxysilane in the presence of the starting organoclay. Later on, pre-formed ZnO nanoparticles (NP) dispersed in 2-propanol were incorporated under ultrasound irradiation to the silica–organoclay hybrid heterostructures dispersed in 2-propanol, and finally, the resulting solids were calcinated to eliminate the organic matter and to produce ZnO nanoparticles (NP) homogeneously assembled to the clay–SiO2 framework. In the case of montmorillonite the resulting materials were identified as delaminated clays of ZnO/SiO2-clay composition, whereas for sepiolite, the resulting heterostructure is constituted by the assembling of ZnO NP to the sepiolite–silica substrate only affecting the external surface of the clay. The structural and morphological features of the prepared heterostructures were characterized by diverse physico-chemical techniques (such as XRD, FTIR, TEM, FE-SEM). The efficiency of these new porous ZnO/SiO2-clay heterostructures as potential photocatalysts in the degradation of organic dyes and the removal of pharmaceutical drugs in water solution was tested using methylene blue and ibuprofen compounds, respectively, as model of pollutants.
Keywords: delamination; montmorillonite; organoclays; photocatalysis; porous clay heterostructures; sepiolite; ZnO nanoparticles

(untitled) - Hariharan, C. (Appl. Catal., A, 2006)

(untitled) - Pauporté, T.; Rathouský, J. (J. Phys. Chem. C, 2007)

(untitled) - Daneshvar, N.; Rasoulifard, M. H.; Khataee, A. R.; Hosseinzadeh, F. (J. Hazard. Mater., 2007)

(untitled) - Daneshvar, N.; Salari, D.; Khataee, A. R. (J. Photochem. Photobiol., A, 2004)

(untitled) - Dindar, B.; Içli, S. (J. Photochem. Photobiol., A: Chem., 2001)

(untitled) - Lizama, C.; Freer, J.; Baeza, J.; Mansilla, H. D. (Catal. Today, 2002)

(untitled) - Wang, Z. L. (J. Phys.: Condens. Matter, 2004)

(untitled) - Khaorapapong, N.; Khumchoo, N.; Ogawa, M. (Mater. Lett., 2011)

(untitled) - Khumchoo, N.; Khaorapapong, N.; Ogawa, M. (Appl. Clay Sci., 2015)

CMS Workshop Lectures Series - Aranda, P.; Belver, C.; Ruiz-Hitzky, E. (Clays and Materials, 2014)

(untitled) - Letaief, S.; Ruiz-Hitzky, E. (Chem. Commun., 2003)

(untitled) - Letaïef, S.; Martín-Luengo, M. A.; Aranda, P.; Ruiz-Hitzky, E. (Adv. Funct. Mater., 2006)

(untitled) - Lagaly, G.; Ogawa, M.; Dékány, I. (Dev. Clay Sci., 2013)

(untitled) - Ruiz-Hitzky, E.; Aranda, P. (J. Sol-Gel Sci. Technol., 2014)

(untitled) - Rhouta, B.; Bouna, L.; Maury, F.; Senocq, F.; Lafont, M. C.; Jada, A.; Amjoud, M.; Daoudi, L. (Appl. Clay Sci., 2015)

(untitled) - Rhouta, B.; Bouna, L.; Maury, F.; Senocq, F.; Lafont, M. C.; Jada, A.; Amjoud, M.; Daoudi, L. (Appl. Clay Sci., 2015)

(untitled) - Gómez-Avilés, A.; Aranda, P.; Fernandes, F. M.; Belver, C.; Ruiz-Hitzky, E. (J. Nanosci. Nanotechnol., 2013)

(untitled) - Belver, C.; Aranda, P.; Ruiz-Hitzky, E. (J. Mater. Chem. A, 2013)

(untitled) - Belver, C.; Aranda, P.; Martín-Luengo, M. A.; Ruiz-Hitzky, E. (Microporous Mesoporous Mater., 2012)

(untitled) - Manova, E.; Aranda, P.; Martín-Luengo, M. A.; Letaïef, S.; Ruiz-Hitzky, E. (Microporous Mesoporous Mater., 2010)

(untitled) - Aranda, P.; Kun, R.; Martin-Luengo, M. A.; Letaïef, S.; Dékány, I.; Ruiz-Hitzky, E. (Chem. Mater., 2008)

(untitled) - Akkari, M.; Aranda, P.; Ben Rhaiem, H.; Ben Haj Amara, A.; Ruiz-Hitzky, E. (Appl. Clay Sci., 2016)

Adsorption by Powders and Porous Solids: Principles, Methodology and Applications - Rouquerol, F.; Rouquerol, J.; Sing, K. (Academic Press, 1999)

(untitled) - Fernandes, F. M.; Manjubala, I.; Ruiz-Hitzky, E. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Sanz, J. (Dev. Clay Sci., 2006)

(untitled) - Letaief, S.; Liu, Y.; Detellier, C. (Can. J. Chem., 2011)

(untitled) - Ahlrichs, J. L.; Serna, J. C.; Serratosa, J. M. (Clays Clay Miner., 1975)

(untitled) - Fatimah, I.; Wang, S.; Wulandari, D. (Appl. Clay Sci., 2011)

(untitled) - Sohrabnezhad, S.; Seifi, A. (Appl. Surf. Sci., 2016)

(untitled) - Choina, J.; Bagabas, A.; Fischer, C.; Flechsig, G.-U.; Kosslick, H.; Alshammari, A.; Schulz, A. (Catal. Today, 2015)

(untitled) - Letaïef, S.; Casal, B.; Kbir-Ariquib, N.; Trabelsi-Ayadi, M.; Ruiz-Hitzky, E. (Clay Miner., 2002)

(untitled) - Ruiz-Hitzky, E. (J. Mater. Chem., 2001)

Elements of X-Ray Diffraction - Cullity, B. D. (Addison-Wesley, 1978)

(untitled) - Lippens, B. C.; de Boer, J. H. (J. Catal., 1965)

(untitled) - Dai, X.-J.; Luo, Y.-S.; Zhang, W.-D.; Fu, S.-Y. (Dalton Trans., 2010)